THE NON LINEAR TRANSMISSION PROBLEM WITH TIME DEPENDENT COEFFICIENTS - Muñoz Rivera, Jaime Edilberto (2006)
In this paper we consider the nonlinear transmission problem for the wave equation with time dependent coefficients and linear internal damping. We prove global existence and exponential decay of solution. The result is achieved by considering energy like - Lyapunov functionals and suitable unique continuation theorem for the wave equation.